Avaliação das atividades antimicrobiana, antioxidante e antineoplásica dos extratos etanólicos da casca e folhas da Terminalia fagifolia Mart. et Zucc (Combretaceae) - Rodrigues, Patrícia Siqueira de Melo (Universidade Federal do Tocantins, 2016)
The search for new therapeutic approaches, such as the ones with medicinal plants, has been raising great interest of the scientific community in the search for more effective treatments for diseases caused by pathogenic microorganisms and more effective cancer therapies. Terminalia fagifolia Mart. et Zucc is a medicinal plant found in the Brazilian Cerrado, commonly used in the treatment of cancer sores and tumors. This study aimed to evaluate the antibacterial and antioxidant activity of the rough ethanolic extracts of the barks and leaves of Terminalia fagifolia and assay the cytotoxic activity of the extracts in normal cell lineages NIH 3T3 and L929 and tumor cell lineages PC3 and B16F10. The antibacterial activity was determined by agar diffusion method by well technique and by the Minimum Inhibitory Concentration (MIC). In the agar diffusion technique the Terminalia fagifolia bark extract showed better antibacterial activity than the extract of the leaves. In the determination of Minimum Inhibitory Concentration, both bark and leave’s extract showed MIC of 75 mg/ml, having thus a good antimicrobial activity, once, in this concentration, they inhibited the growing of bacterial inoculum in 100% and more than 90%, respectively. The evaluation of the cytotoxic activity was investigated by MTS assay. The obtained results showed that the extracts has cell viability for normal cells NHI 3T3 and L929 and cytotoxicity for tumor cells PC3 and B16F10. Thus, it becomes necessary to continue the studies with this plant, once both extracts showed very promising antimicrobial and antitumor activities.